ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SECARA ONLINE PADA SITUS LAZADA DI KALANGAN MAHASISWA FAKULTAS EKONOMI UNES-AAI PADANG - Friska Adriyawati; Yulistia; Agussalim M (LPPM Universitas Ekasakti, Padang, 2021)
This Research Result Aims To Research And Analyze The Analysis Of Factors Affecting Online Purchasing Decisions On Lazada Sites Among Students Faculty Of Economics, Padang Unes-Aai Where Variable X1 Is Price, X2 Promotion X3 Brand Image And X4 Trust, Dependent Variable Is Purchasing Decision . This Research Uses Classical Assumption Test Consisting Of Normality Test, Multicircular Priority Test, Heroskadisity Test and Multiple Regression Test, T Test and F Test. The results of this study are partially variable X1 is price, X2 promotion X3 brand image and X4 trust, positive and significant effect on online purchase decisions on Lazada sites among students of the Faculty of Economics Unes-AAI Padang. Simultaneously Variable X1 is price, X2 promotion X3 brand image and X4 positive and significant trust towards Online Purchase Decisions on Lazada Sites Among Students of the Faculty of Economics Unes-AAI Padang